2013
DOI: 10.1021/ja311400t
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Water on the Electronic Structure of Firefly Oxyluciferin Anions from Absorption Spectroscopy of Bare and Monohydrated Ions in Vacuo

Abstract: A complete understanding of the physics underlying the varied colors of firefly bioluminescence remains elusive because it is difficult to disentangle different enzyme-lumophore interactions. Experiments on isolated ions are useful to establish a proper reference when there are no microenvironmental perturbations. Here, we use action spectroscopy to compare the absorption by the firefly oxyluciferin lumophore isolated in vacuo and complexed with a single water molecule. While the process relevant to biolumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 65 publications
4
87
1
Order By: Relevance
“…[21] The range-separated CAM-B3LYP functional [22,23] was chosen as this has previously been shown [24] to provide results similar to those obtained with the computationally demanding equation of motion coupled-cluster level of theory. [21] The range-separated CAM-B3LYP functional [22,23] was chosen as this has previously been shown [24] to provide results similar to those obtained with the computationally demanding equation of motion coupled-cluster level of theory.…”
Section: Methodsmentioning
confidence: 99%
“…[21] The range-separated CAM-B3LYP functional [22,23] was chosen as this has previously been shown [24] to provide results similar to those obtained with the computationally demanding equation of motion coupled-cluster level of theory. [21] The range-separated CAM-B3LYP functional [22,23] was chosen as this has previously been shown [24] to provide results similar to those obtained with the computationally demanding equation of motion coupled-cluster level of theory.…”
Section: Methodsmentioning
confidence: 99%
“…One bioluminescent reaction system with a particularly high quantum yield is that of fireflies, which has been the topic of many recent experimental and theoretical studies . However, despite that much progress has been made in the elucidation of the mechanisms underlying the light emission of fireflies, many details of the luciferase‐catalyzed formation of the chemiexcited (S 1 , first excited singlet state) oxyluciferin emitter (OxyLH 2 ) from d ‐luciferin (LH 2 , a ground‐state species), are yet to be resolved. As shown in Figure and described in detail elsewhere, this conversion is initiated by adenylation of LH 2 with ATP‐Mg 2+ , which forms d ‐luciferyl‐adenylate (LH 2 ‐AMP).…”
Section: Introductionmentioning
confidence: 99%
“…An environment can provide an efficient way of protection by energy dissipation [10]. The dissociation time of the isolated photoexcited ions in vacuo is about 100 s based on previous storage-ring experiments [11], which results in a dissociation yield of 10 -6 -10 -8 assuming a time constant for vibrational cooling between 1 ps and 100 ps. Each flash from a firefly contains about 10 13 photons [12], and the same order of magnitude of hot ions is therefore produced (59 % yield versus 41 %).…”
Section: Introductionmentioning
confidence: 99%
“…A wavelength of 550 nm was used as we have earlier found that this is the maximum of the absorption band [11]. For each of the identified fragments, we calculated the reaction energy associated with the dissociation channel to see if the reaction would be possible or not for A c c e p t e d M a n u s c r i p t 4 vibrationally excited (hot) oxyluciferin ions within the luciferase enzyme.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation